Environmental taxation and mergers in oligopoly markets with product differentiation. - Fikru, Mahelet G.; Gautier, Luis (Springer, 2017)
We analyze the effect of mergers on optimal environmental taxation in a Cournot oligopoly market with product differentiation. Our result indicates that the adjustment in emission tax crucially depends on the post-merger output distortion and pollution intensities. Specifically, we find that the optimal emission tax increases postmerger as long as pollution intensity of firms is higher and output distortion smaller post-merger than pre-merger. Furthermore, our result suggests that there is no need to revise environmental policy in markets where pollution intensity of firms does not change post-merger and (i) products are completely differentiated, or (ii) there are many firms for any degree of product differentiation.
Política de acceso abierto tomada de: https://v2.sherpa.ac.uk/id/publication/16656
Keywords: Impuestos ambientales; Oligopolios; Sociedades - Fusión; Emission tax; Output distortion; Mergers and acquisitions; Pollution intensity; End-of-the-pipe abatement; Carbon tax